2018
DOI: 10.1016/j.biocel.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of targeting the Eph/ephrin signaling complex

Abstract: The Eph-ephrin signaling pathway mediates developmental processes and the proper functioning of the adult human body. This distinctive bidirectional signaling pathway includes a canonical downstream signal cascade inside the Eph-bearing cells, as well as a reverse signaling in the ephrin-bearing cells. The signaling is terminated by ADAM metalloproteinase cleavage, internalization, and degradation of the Eph/ephrin complexes. Consequently, the Eph-ephrin-ADAM signaling cascade has emerged as a key target with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 180 publications
(237 reference statements)
0
24
0
Order By: Relevance
“…Although early Notch activation can bestow positional determination, this does not irrevocably commit cells to an arterial fate. Lineage-tracing studies reveal that Notch-activated cells initially and positionally committed to the dorsal aorta can later become venous tissue by de-or transdifferentiation [17].…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…Although early Notch activation can bestow positional determination, this does not irrevocably commit cells to an arterial fate. Lineage-tracing studies reveal that Notch-activated cells initially and positionally committed to the dorsal aorta can later become venous tissue by de-or transdifferentiation [17].…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…It has been reported that the G-H loop region in the C-terminal domain of azurin (aa 96-113) has structural similarity to ephrinB2 at the G-H loop region, which has a role in receptor binding. Additionally, azurin could interfere in autophosphorylation of the tyrosine residue in the kinase domain of EphB2 resulting in the prevention of tumor progression and in cancer growth inhibition (30,31). One previous study reported that azurin is also able to decrease the signaling of the FAK/Src complex, which mediates the decrease in the expression of P-cadherin at the cellular membrane and represses the growth of breast cancer cells with highly invasive P-cadherin overexpression.…”
Section: About Azurinmentioning
confidence: 99%
“…Antibodies, interfering RNAs (iRNAs), peptides, soluble fragments of Eph/ephrin, and small molecules -including protein-protein interaction inhibitor (PPIs) and kinase inhibitors -have been used. Since reviews summarizing therapeutic-oriented strategies are available in the literature [6,[80][81][82], we will here focus on recently developed tools targeting EphA receptors.…”
Section: Targeting Epha Receptorsmentioning
confidence: 99%
“…Like peptides, recent efforts have been focused on optimizing existing PPI inhibitors since most of them exhibit lack of specificity and stability, as well as weak bioavailability [131]. PPI inhibitors targeting EphAs have been reviewed recently [82]. Recent improvements are summarized here.…”
Section: Small Moleculesmentioning
confidence: 99%